Contrastes cualitativos entre palmas de aceite sin síntomas y con síntomas de producción de cogollo en la zona palmera occidental Qualitative contrasts among apparently healthy and disease oil palms with rot heart in the western palm zone - Enríquez C, Gabriel; Bastidas L, Edison; Bastidas P, Silvio (Revista de Ciencias Agrícolas, 2008)
La investigación se realizó en las plantaciones Palmas de Tumaco y Corpoica Estación Experimental El Mira ubicadas en Tumaco, con el propósito de identificar cualidades indicadoras de palmas predispuestas a ser afectadas por la enfermedad pudrición del cogollo (CPC). Se usaron palmas de aceite (Elaeis guineensis Jacq.) de diferente origen genético y edad. De cada material fueron caracterizadas cuatro palmas con síntomas de CPC y dos aparentemente sanas, con base en 11 descriptores morfológicos cualitativos. Los datos de campo se analizaron mediante Análisis Multivariados por Correspondencias Múltiples (ACM). Los descriptores estudiados no presentaron diferencias entre una palma aparentemente sana y una enferma, por lo tanto ninguno está asociado con la predisposición al CPC, indicando que CPC no tiene capacidad para modificar o deformar ninguna cualidad morfológica externa de la palma. Se encontró que las cuatro correspondencias primeras explican 56.28% de la variabilidad, indicando bajo poder discriminante de los descriptores. El ACM permitió la conformación de dos grupos, cada uno manifiesta un estado contrastante de las características doble estado. ABSTRACT The investigation was carried out at Palmas de Tumaco and Corpoica El Mira Research Station located in Tumaco area, western palm zone, with the purpose to identify qualities indicative of potentially predisposed palms to the rot heart disease (CPC). Oil palms (Elaeis guineensis Jacq.) of different genetic origin and age were used in the study. For each type of genetic material were characterized four palms sick with CPC and two apparently healthy palms, in accordance with 11 qualitative morphological describers. Qualitative data obtained in field, were analyzed with Multivariate Analysis by Multiple Correspondences Analysis (ACM) to establish differences among apparently healthy palms and diseases palms with CPC within materials, and to form groups by hierarchical classification. The studied qualitative describers did not to identify differences between diseases palms with CPC and healthy palms. Not any describers were associated with the predisposed palms to the CPC, indicating CPC has not capacity to modify or to deform anything morphological quality external of the palm. According to the Multiple Correspondence Analysis, the four multiple correspondences explain 56.28% of the variability observed in the genetic materials, indicating low power discriminate of the qualitative describers studied. Multiple Correspondence Analysis permit conform two groups in the studied materials, each one presented a contrasting stage of the characteristics double stage: leafs with or less inflorescences, presence or absence of fibers on bunch, presence or absence of deceased bunches and bunch peduncle large or short.